Pembelajaran Penggunaan Microsoft Office Yang Baik Dan Terorganisir - Joosten Joosten; Caroline Caroline; Elly Elly (STMIK Royal, 2023)
Abstract: One of the IT applications utilized by the community is Microsoft Office. This application helps various parties in supporting the learning process in schools and is used by various parties for office work needs in processing words, numbers and presentations. Understanding and mastering this application is a basic ability that must be owned by every individual in the present. As is the case with students at SMA Letjen Haryono MT while studying at school. However, the use of Office has not been maximized by them. They were only introduced to Microsoft Office applications but did not understand how to use them. Therefore, students need to be equipped with additional learning that focuses on using Microsoft Office as a medium to assist student learning and also prepares students to take advantage of this application in the future. The features available in Microsoft Word, Microsoft Excel, and Microsoft Power Point are also less known by students. Departing from this, it is necessary to equip students with learning about Microsoft Office applications. Learning activities provide a range of 77% through questionnaires filled out by students which means that the training provided provides good knowledge benefits to the 28 students who take part in the training. The target planned by the implementation team was achieved where students were assisted in understanding and learning to use Microsoft Word, Microsoft Excel and Microsoft Power Point applications. Keywords: education; information technology; microsoft office Abstrak: Salah satu penerapan TI yang dimanfaatkan oleh masyarakat adalah Microsoft Office. Aplikasi ini membantu berbagai pihak dalam mendukung proses pembelajaran di sekolah serta dimanfaatkan berbagai pihak untuk kebutuhan pekerjaan kantoran dalam pengolahan kata, angka serta presentasi. Pemahaman dan penguasaan aplikasi ini merupakan kemampuan dasar yang wajib dimiliki oleh tiap individu di masa sekarang. Seperti halnya dengan murid-murid di SMA Letjen Haryono MT selama belajar di sekolah. Tetapi, penggunaan Office belum dimaksimalkan oleh mereka. Mereka hanya diperkenalkan aplikasi Microsoft Office tetapi kurang memahami cara penggunaannya. Oleh karena itu, maka murid perlu dibekali dengan pembelajaran tambahan yang berfokus pada penggunaan Microsoft Office sebagai media untuk membantu pembelajaran murid dan juga mempersiapkan murid manfaatkan aplikasi ini di masa mendatang. Fitur-fitur yang tersedia di Microsoft Word, Microsoft Excel, dan Microsoft Power Point juga kurang diketahui oleh murid-murid. Berangkat dari hal tersebut, maka perlu melengkapi murid dengan pembelajaran akan aplikasi Microsoft Office. Kegiatan pembelajaran memberikan nilai range 77% lewat kuesioner yang diisi murid yang berarti pelatihan yang diberikan memberikan manfaat pengetahuan yang baik kepada 28 murid yang mengikuti pelatihan. Target yang direncanakan tim pelaksana tercapai di mana murid-murid terbantu dalam memahami dan mempelajari penggunaan aplikasi Microsoft Word, Microsoft Excel, dan Microsoft Power Point.Kata kunci: pendidikan; teknologi informasi; microsoft office